Recruitment of Schools for Intervention Research to Reduce Health Disparities for Sexual and Gender Minority Students. (August 2020) - Shattuck, Daniel; Hall, Janie Lee; Green, Amy; Greenberg, Cynthia; Peñaloza, Linda; Ramos, Mary; Willging, Cathleen
Recruiting schools for intervention research can be daunting. This study examined the experiences of researchers recruiting public high schools for a randomized controlled trial to reduce suicide disparities for sexual and gender minority (SGM) youth by implementing evidence-based strategies to enhance school environments. We enrolled 42 schools throughout New Mexico between August 2016 and April 2017. Based on qualitative analysis of recruitment efforts, three groups of factors affected enrollment: (1) non-SGM-specific factors, (2) SGM-specific factors, and (3) facilitating factors. Non-SGM-specific factors negatively impacted the willingness or ability to participate (e.g., demanding staff workloads and beliefs that "outsiders" should not assist with school-based interventions). Notable SGM-specific factors centered on influences in socially conservative community environments and beliefs that schools lacked SGM students. Advocacy, leveraging relationships, and persistence were facilitating factors for overcoming recruitment obstacles. Our findings have implications for researchers and school nurses interested in school-based interventions, especially those focused on SGM youth.